MARKOV CHAIN TO CONTROL GENERIC DRUG IN INVENTORY PROBLEM - Marlina Setia Sinaga; Hamidah Nasution; Oktariani Purba; Lasker Pangarapan Sinaga (Universitas Negeri Medan, 2019)
Abstract: Have the generic drugs inventory been optimal, neither excessive nor deficient? Inadequate inventory can cause in losses due to increased ordering and storage costs. Shortage of generic drug will cause a decrease of public health services. Given demand generic drugs which always fluctuates, so stochastic process is the right method. In this study, the optimal level of generic drugs inventory will be analyzed by using the Markov chain. Steady state conditions were achieved when the same results obtained with the previous iteration result. There are 7 linear equations produced, each accompanied by 7 levels of inventory, optimal order quantities and also the costs.Keywords: Demand; Generic Drug; Inventory; Markov Chain.Abstrak: Apakah persediaan obat generik sudah optimal, tidak berlebih maupun kekurangan? Persediaan yang tidak optimal dapat mengakibatkan kerugian akibat bertambahnya biaya pemesanan maupun biaya penyimpanan. Kekurangan persediaan obat generik bahkan juga akan mengakibatkan turunnya tingkat layanan kesehatan masyarakat. Mengingat tingkat permintaan obat generik yang berfluktuasi maka proses stokastik menjadi pilihan metode yang tepat. Pada penelitian ini, tingkat persediaan obat generik yang optimal akan dianalisis dengan menggunakan markov chain. Kondisi steady state tercapai ketika hasil yang sama diperoleh dengan hasil dari iterasi sebelumnya. Ada 7 persamaan linier yang dihasilkan, masing-masing disertai dengan 7 tingkat persediaan dan besaran pemesanan optimal dan juga besaran biaya.Kata kunci: Permintaan, Obat Generik; Persediaan; Rantai Markov